Factors influence consumer decision making in purchasing mobile phone in Sibu - Tiew, Sing Lui (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The purpose of this study is to identify the factors influence consumer decision making in purchasing mobile phone in Sibu. This study examines the seven main factors which are price, product, promotion, social, cultural, place and family will influence most to the consumer decision making.